Major Bottom Water Ventilation Events Do Not Significantly Reduce Basin-Wide Benthic N and P Release in the Eastern Gotland Basin (Baltic Sea) - Sommer, Stefan; Clemens, David; Yücel, Mustafa; Pfannkuche, Olaf; Hall, Per O. J.; Almroth-Rosell, Elin; Schulz-Vogt, Heide N.; Dale, Andrew W. (Frontiers in Marine Science, 2017)
Redox-sensitive mobilization of nutrients from sediments strongly affects the eutrophic state of the central Baltic Sea; a region associated with the spread of hypoxia and almost permanently anoxic and sulfidic conditions in the deeper basins. Ventilation of these basins depends on renewal by inflow of water enriched in oxygen (O2) from the North Sea, occurring roughly once per decade. Benthic fluxes and water column distributions of dissolved inorganic nitrogen species, phosphate (PO43-), dissolved inorganic carbon (DIC), sulfide (HS-) and total oxygen uptake (TOU) were measured along a depth gradient in the Eastern Gotland Basin (EGB). Campaigns were conducted during euxinic conditions of the deep basin in Aug./Sept. 2013 and after two inflow events in July/Aug. 2015 and March 2016 when O2 concentrations in deep waters reached 60 µM. The intrusion of O2-rich North Sea water into the EGB led to an approximate 33 % and 10 % reduction of the seabed PO43- and ammonium (NH4+) release from deep basin sediments. Post-inflow, the deep basin sediment was rapidly colonized by HS- oxidizing bacteria tentatively assigned to the family Beggiatoaceae, and HS- release was completely suppressed. The presence of a hypoxic transition zone (HTZ) between 80 and 120 m water depth was confirmed not only for euxinic deep-water conditions during 2013 but also for post-inflow conditions. Because deep-water renewal did not ventilate the HTZ, where PO43- and NH4+ fluxes were highest, high seabed nutrient release there was relatively unchanged. Extrapolation of the in situ nutrient fluxes indicated that, overall, the reduction in PO43- and NH4+ release in response to deep-water renewal can be considered as minor, reducing the internal nutrient load by 2 and 12 % only, respectively. Infrequent inflow events thus have a limited capacity to sustainably reduce internal nutrient loading in the EGB and mitigate eutrophication.